2021
DOI: 10.1557/s43580-021-00045-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of new Fe–Al–Nb(–B) alloys for structural applications at high temperatures

Abstract: It is known for Fe–Al–Ta alloys, that a homogeneous distribution of strengthening Laves phase precipitates in the matrix and aligned at the grain boundaries can be obtained when the formation of the stable Laves phase is preceded by the formation of the metastable Heusler phase. Several Fe–Al–Nb alloys with different Al and Nb contents and with or without boron doping are studied to elucidate whether comparable microstructures can be obtained in this system. It was found that the Heusler phase only occurs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…This explains why in a preceding study the metastable Heusler phase has only been observed in an alloy with about 25 at.% Al. [37] Iron aluminide based alloys are well suited for casting parts. [3] The good casting properties of these materials are partly due to the small difference between liquidus and solidus temperatures, which helps to avoid residual coring during casting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This explains why in a preceding study the metastable Heusler phase has only been observed in an alloy with about 25 at.% Al. [37] Iron aluminide based alloys are well suited for casting parts. [3] The good casting properties of these materials are partly due to the small difference between liquidus and solidus temperatures, which helps to avoid residual coring during casting.…”
Section: Discussionmentioning
confidence: 99%
“…Fe-31Al-3Nb-0.06B [37] 65.6 ± 0.3 32.5 ± 0.3 1.9 ± 0.2 0.94 52.7 ± 1.0 22.1 ± 0.6 25.2 ± 0.7 0.06 Fe-33.6Al-3Nb [37] 64.2 ± 0.6 33.6 ± 0.4 2.2 ± 0.2 0.96 52.0 ± 0.9 23.1 ± 0.6 24.9 ± 0.7 0.04 Fe-33.6Al-3Nb-0.03B [37] 63.1 ± 0.4 34.4 ± 0.1 2.5 ± 0.3 0.97 51.5 ± 1.5 23.5 ± 0.6 25.0 ± 1.8 0.03 actual compositions of the alloys and their slope changes continuously, indicating that equilibrium has been attained in all samples and that there is no conflict between individual measurements. In Fig.…”
Section: Partial Isothermal Section At 700 °Cmentioning
confidence: 99%
See 3 more Smart Citations